Effectiveness of traditional Chinese medicine music therapy on anxiety and depression emotions of lung cancer patients: A protocol for systematic review and meta-analysis. Issue 12 (26th March 2021) - Jiang, Xiaolin; Gao, Jing; Zheng, Yuping
Abstract: Background: Lung cancer patients often accompanied with severe depression and anxiety emotions, and those negative emotions could affects the treatment and recovery of the illness, decrease the patients' quality of life. In recent years, traditional Chinese medicine five-element music therapy (TCM-FEMT) is widely used for psychological problems of lung cancer patients for its unique advantages, TCM-FEMT applied to negative emotions management of lung cancer patients has been reported in many publications, but there is lacks evidence-based medicine, in this study, effectiveness of TCM-FEMT on anxiety and depression emotions of lung cancer patients will be systematically evaluated. Methods: PubMed, the Cochrane Library, Web of Science, Embase, Chinese Biomedical Literature Database, China National Knowledge Infrastructure, VIP Database, WanFang Database were electronically searched to collect RCTs on the efficacy of TCM-FEMT on anxiety and depression emotions of lung cancer patients from inception to February 2021. In addition, retrospect the references of the included literature to supplement the relevant literature. Research selection, data extraction and quality evaluation of literature will be carried out by 2 researchers, respectively. RevMan 5.3 software will be used for statistical analysis. Results: This study will comprehensively summarize the current trials to determine the effectiveness of TCM-FEMT on anxiety and depression emotions of lung cancer patients. Conclusion: This study will provide comprehensive evidence for the efficacy of TCM-FEMT on anxiety and depression emotions of lung cancer patients.